ANALISIS FASIES BATUAN SEDIMEN SERTA HUBUNGANNYA DENGAN PARAMETER KUALITAS BATUBARA BERDASARKAN ANALISIS UJI PROKSIMAT PADA LAPANGAN EKSPLORASI PT ANUGERAH LUMBUNG ENERGI, TAMBANG KINTAP, KABUPATEN TANAH LAUT, PROVINSI KALIMANTAN SELATAN - Yudistira Aji Sasongko (Geological Engineering E-Journal, 2014)
Asam-asam Basin is one of the basins where to be found good quality coals in Kalimantan, especially in the the Eocene Tanjung Formation. The studies of Tanjung Formation have been done by other researchers, but study devoted to the Tanjung Formation of Asam-asam Basin has not been done yet. The purpose of this study was to determine the lithological characteristics found in the study sites, geological structure, sedimentary rock facies, as well as studies about the relationship between sedimentary rock facies with quality parameters of coal based on laboratory proximate test analysis. The study was conducted using descriptive methods include case study research and direct observation in the field through geological mapping and stratigraphic measurements, as well as analysis method include performed data processing as a result of field observation and other supporting data. The processed data is presented in the form of lithology columns, maps, and data of geological structure. After that performed the laboratory analysis includes analysis of sedimentary facies and structural analysis of geology. In the final stage is the interpretation of sedimentary facies and their relationship with quality parameters of coal based on proximate test analysis. Based on the results of research, it is known that geological structures that develop in area of research are systematical joints with main force direction North-Northeast (NNE) - South-Southwest (SSW), normal faults with a trending fault plane Southwest - Northeast , as well as the reverse fault with a trending fault plane Northwest - Southeast. From the facies analysis, rocks of older age at study sites are sedimented on transitional lower delta plain environment, with sub-environment includes swamp, interdistributary bay, distributary channels, and crevasse splay; whereas the younger rocks are sedimented in the lower delta plain environment, with sub-environment includes swamp, interdistributary bay, distributary channel, crevasse splay, and tidal flats. There are 11 coal seams exposed as the results of the field observations, from the oldest to the youngest age are seam L2, L1, L30, M25, M50, and M30 whose are sedimented in the transitional lower delta plain environment, also seam R1, R15, R2, R 3-1 and R 3-2 whose are sedimented in the lower delta plain environment. Based on the proximate analysis test, it is known that : ash values ranged 7-50%, classified as moderate to high (Graese, 1992); sulfur total values ranged from 0.34 to 1.06%, classified as moderate to high category (Hunt, 1984); and calorific value ranges from 2836 - 6693 kcal/kg, and the relatively low quality coal to high quality (Directorat General of Mineral and Coal, 2011; within Indonesian Coal Resources Development and Future Direction Of Coal Export). Based on the value of ash (ash content), total sulfur, and calorific value, it is known that in general, the coal seams whose sedimented at the transitional lower delta plain environment have better quality than the coal seams of lower delta plain environment.